Evolução das práticas de governança corporativa e desempenho das empresas brasileiras de capital aberto não listadas em bolsa - Almeida, Moisés Araújo (2008)
The adoption of good practical of corporate governance opens space for a more transparent management, decrease the asymmetry of information and the conflict of agency, making possible the maximization of value in the company. The main objective of this study is to investigate evolution and the determinants of quality of practical of corporate governance, as well analyzing if relation exists between the quality of these practical of governance and the performance of nonlisted the Brazilian companies of open capital in stock exchange, in period between 2003 and 2007. The sample is composed for 120 companies in 2003, 53 companies in 2004, 94 companies in 2005, 79 companies in 2006 and 64 companies in 2007. The data had been collected directly of System DIVEXT and the use of econometrical techniques of multiple linear regression. The results had shown that the nonlisted open companies are predominantly of familiar property and they are more frequently in the regions Southeastern and South. Relating to the determinants of practical of corporate governance, it was verified that the performance and the size of the company positively influence the pointer of the quality of the practical of corporate governance. The results also indicate a positive relation enter the quality of the corporate governance and the return on the assets of the company, confirming that better practical of governance tend to present in better performance.